A Contribution to the History of Architectural and Environmental Representation (diségno, 2018)
It is necessary to reflect on the meaning of the term ‘Architectural Representation’ before tackling the themes related to its history over the centuries; this denomination was fully accepted into technical language only in relatively recent times, starting from the middle of the last century, while previously other terms were used, such as ‘drawing’, ‘architectural drawing’, ‘technical drawing’, ‘descriptive geometry’, ‘applications of descriptive geometry’, ‘methods of representation’ (read more).